PENGEMBANGAN MEDIA DAN INOVASI MEDIA YANG DIPROYEKSIKAN - Muhammad Hafid; Mardia Hayati (STKIP Subang, 2026)
This study aims to explore the development and innovation of projected learning media, specifically PowerPoint (PPT), in enhancing the quality of Islamic Religious Education (PAI). The primary issue in PAI learning is the presentation of material that often appears rigid and the difficulty of visualizing abstract concepts. This research employs a library research method with content analysis techniques to synthesize various theories and research findings related to projection media. The results indicate that the development of educative PPT must fulfill visual design principles (simplicity, hierarchy, and contrast) as well as technical multimedia principles to improve students' memory retention through dual coding. Media innovation in the digital era includes the use of interactive features, Artificial Intelligence (AI) integration, and cloud-based collaboration. The conclusion of this study confirms that innovation in projected media is capable of transforming PAI learning into a more interactive experience, increasing learning motivation, and assisting teachers' time management efficiency in the classroom. Keywords: Projected Media, PowerPoint, Learning Innovation, Islamic Religious Education, Digital Era.